Simulasi Sistem Monitoring Arus Lebih Pada Jaringan PLN Satu Fasa Menggunakan Web Berbasis Mikrokontroller - Yul Antonisfia; Muhammad Irmansyah; Anggara Nasution (Elektron : Jurnal Ilmiah, 2018)
Modernization is indeed very influential in the lives of people today, with the existence of this modern era, everything is always related to technology. The place is far enough and to find out the condition of the excess current makes the PLN officials also have difficulty because there is no monitoring tool from the situation. From the description above, the author found the idea to make a Simulation System for Monitoring Overcurrent Systems in the PLN Phase One Phase Using a Microcontroller-Based Web. The tool uses the Arduino Mega microcontroller coupled with ACS712 Flow sensors, and Ethernet Shield Modules. The way this tool works is to detect the electric current that enters the Input from the electrical equipment load on the ACS712 sensor. In testing the author only uses 3 pieces of light as a burden to determine the state of excess current. If you use 1 load, the current that is read is 0.44A with a 100 Watt lamp power. And if the load is added by 1 load with 75 Watt of light power, the current that is read becomes 0.77A. Then the load is added with 1 lamp with a power of 60 Watt, then the current becomes 1.05A with the result at all three drop loads.